2018
DOI: 10.1016/j.jhsa.2018.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Cost Implications of Varying the Surgical Technique, Surgical Setting, and Anesthesia Type for Carpal Tunnel Release Surgery

Abstract: This study identifies modifiable factors that may lead to cost reductions for CTR surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 20 publications
6
90
0
1
Order By: Relevance
“…In our multivariable regression analysis of patients treated in the OR, we observe that use of BB/regional or MAC anesthesia significantly reduced surgical costs by 30 and 24%, respectively, as compared with general anesthesia. Although no prior literature exists to our knowledge that is specific to DQR, these results mirror those for carpal tunnel release 14,27 and trigger digit release. 20…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In our multivariable regression analysis of patients treated in the OR, we observe that use of BB/regional or MAC anesthesia significantly reduced surgical costs by 30 and 24%, respectively, as compared with general anesthesia. Although no prior literature exists to our knowledge that is specific to DQR, these results mirror those for carpal tunnel release 14,27 and trigger digit release. 20…”
Section: Discussionsupporting
confidence: 63%
“…In another study evaluating costs associated with anesthesia services for small hand surgeries, Kamnerdnakta et al concluded that such services may not be medically indicated but account for substantial costs for low-risk patients undergoing minor hand surgeries, including DQRs. 25 Although not specific for DQR, other studies have demonstrated significant and substantial cost savings associated with performing carpal tunnel release 14,26 and trigger digit release 20 in the PR setting as opposed to the OR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations